2020
DOI: 10.3390/ani10081401
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Slow-Growing Management Systems: Characterisation of Broiler Caecal Microbiota Development throughout the Growing Period

Abstract: Caecal microbiota and its modulation play an important role in poultry health, productivity and disease control. Moreover, due to the emergence of antimicrobial-resistant bacteria, society is pressing for a reduction in antibiotic administration by finding effective alternatives at farm level, such as less intensified production systems. Hence, the aim of this study was to characterise the caecal microbiota in two different broiler management systems, fast and slow-growing, using 16S rRNA sequencing analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…Essentially, this microbial population is initiated during early development with a consistent array of members being in place after food intake has been established ( Lu et al., 2003 ; Rehman et al., 2007 ). Montoro-Dasi et al. (2020) examined the cecal microbiota of broilers raised under 2 separate management systems that created a difference in live performance.…”
Section: Gastrointestinal System and V-helix-fa Complexesmentioning
confidence: 99%
“…Essentially, this microbial population is initiated during early development with a consistent array of members being in place after food intake has been established ( Lu et al., 2003 ; Rehman et al., 2007 ). Montoro-Dasi et al. (2020) examined the cecal microbiota of broilers raised under 2 separate management systems that created a difference in live performance.…”
Section: Gastrointestinal System and V-helix-fa Complexesmentioning
confidence: 99%
“…There were statistically significant differences in microbiota diversity between farm conditions at slaughter day (42 days of age), when OFC showed a high diversity level. It is well demonstrated that a greater complexity of the gut microbiota is observed as animals grow and that gut microbiota becomes relatively stable as of the mid-period [26,[41][42][43][44][45]. However, overcrowding and heat stress present at the end of the growing period usually induce oxidation alteration, which is closely related to intestinal barrier integrity, which is in turn related to gut microbiota [24,[46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…16S rRNA gene amplification and MiSeq sequencing was performed according to Montoro-Dasi et al [26].…”
Section: S Rrna Gene Amplification and Miseq Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Gut microbes produce various essential metabolites that play vital roles in nutrient digestion, metabolism, and immunity modulation ( Hou et al 2016 ). Furthermore, caecal microbiota and its modulation are closely associated with poultry health, productivity, and disease control (Montoro- Dasi et al 2020 ). The environmental temperature could affect the composition of intestinal microbiota ( Wang et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%